The Activity Platform - Wang, Helen; Moshchuk, Alexander; Gamon, Michael; Haraty, Mona; Iqbal, Shamsi; Brown, Eli T.; Kapoor, Ashish; Meek, Chris; Chen, Eric; Tian, Yuan; Teevan, Jaime; Czerwinski, Mary; et al. (USENIX 15th Workshop on Hot Topics in Operating Systems (HotOS XV), 2015)
In this paper, we advocate “activity” to be a central abstraction between people and computing instead of applications. We outline the vision of the activity platform as the next-generation social platform.